2020
DOI: 10.3389/fnbeh.2020.00086
|View full text |Cite
|
Sign up to set email alerts
|

Forced Abstinence From Alcohol Induces Sex-Specific Depression-Like Behavioral and Neural Adaptations in Somatostatin Neurons in Cortical and Amygdalar Regions

Abstract: Forced abstinence (FA) from alcohol has been shown to produce a variety of anxietyand depression-like symptoms in animal models. Somatostatin (SST) neurons, a subtype of GABAergic neurons found throughout the brain, are a novel neural target with potential treatment implications in affective disorders, yet their role in alcohol use disorders (AUD) remains to be explored. Here, we examined the neuroadaptations of SST neurons during forced abstinence from voluntary alcohol consumption. Following 6 weeks of two-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 67 publications
3
28
2
Order By: Relevance
“…We previously reported that PL SST neurons are hyperexcitable following prolonged withdrawal from alcohol drinking (> 4 weeks) in a 2-bottle choice model (34), which contrasts with the hypoexcitable state in acute withdrawal (24-h) from DID observed here. It should be noted that the excitability recording in the former report was done following an acute stressor (forced swim).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…We previously reported that PL SST neurons are hyperexcitable following prolonged withdrawal from alcohol drinking (> 4 weeks) in a 2-bottle choice model (34), which contrasts with the hypoexcitable state in acute withdrawal (24-h) from DID observed here. It should be noted that the excitability recording in the former report was done following an acute stressor (forced swim).…”
Section: Discussioncontrasting
confidence: 96%
“…Whole cell voltage clamp and current clamp recordings were conducted in the PL similarly to those previously published (spontaneous excitatory and inhibitory postsynaptic currents, sEPSCs and sIPSCs respectivelu, and intrinsic excitability (20,21,34); confirmation of DREADD expression and function (30)). The PL was identified according to the Allen Mouse Brain Atlas.…”
Section: Electrophysiologymentioning
confidence: 99%
“…A caveat is that the majority of these preclinical studies have been conducted in male subjects. In studies that have looked at sex-dependent neuronal response differences in models of alcohol dependence and/or stress, examples of sex-divergent responses are numerous (Morales et al, 2018;Blume et al, 2019;Dao et al, 2020;Joffe et al, 2020;Kasten et al, 2020). The BLA is a brain region of particular interest in this context, given that it sends a strong excitatory projection to the vHC that, when activated, elicits anxiogenesis (Felix-Ortiz and Tye, 2014;Beyeler et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest repeated swim stress makes BNST Pdyn cells more excitable. Others have found that ventral BNST somatostatin cells have increased rheobase, reduced AP threshold, and reduced number of action potentials during protracted abstinence from EtOH, suggestive of GABAergic disinhibition (Dao et al 2020). Our lab recently has shown that withdrawal from chronic intermittent EtOH increases neuronal excitability of BNST CRF neurons, which overlap with Pdyn neurons in the dBNST (Pati et al 2020).…”
Section: Glutamatergic Plasticity Of Bnst Pdyn Cellsmentioning
confidence: 63%